Hyperpolarized noble gases as biomarkers for pulmonary pathology - Lesbats, Clémentine (2017)
Hyperpolarized noble gas MRI using 3He and 129Xe has allowed void space imaging of the lungs for several years. Hyperpolarized 83Kr MRI has also been shown to provide an MRI contrast sensitive to the surface-to-volume ratio and chemistry of synthetic porous systems. Ex vivo animal models of pulmonary diseases and in vitro experiments were used in this thesis to examine three methodological advances allowing for the measurement of pulmonary physiological parameters using 129Xe and 83Kr.